Consumer acceptability analysis of mocaf flour-based noodles sacha inchi seed dregs flour substitution - Ayes Lesmana; Yudhiet Fajar Dewantara (Institute of Computer Science (IOCS), 2023)
Noodles are one of the food products that are very popular, of course, by people in Indonesia. Besides being popular, noodle products are used as alternative food products to replace rice. The data collection method in this study used quantitative methods. The population in this study is staff who work in the kitchen section of Hotel Borobudur Jakarta for limited panelists. Then there are Kartini Elementary School students for untrained panelists. In consumer acceptance, a portion-level test is carried out to determine whether panelists eat out the food provided or not. This test measures the amount and lack of food served when provided. The portion level test was carried out on 5 limited panelists who were kitchen section staff of Hotel Borobudur Jakarta and 50 panelists of children who were students of Kartini Jakarta Elementary School. The highest level of preference in the manufacture of dry noodle products made from MOCAF flour, the substitution of sacha inchi seed pulp flour with 85% MOCAF flour formulation and 15% sacha inchi seed pulp flour.